Promoter Methylation Status of Ras-Association Domain Family Members in Pheochromocytoma - Richter, Antje M.; Zimmermann, Tobias; Haag, Tanja; Walesch, Sara K.; Dammann, Reinhard H. (Frontiers in Endocrinology, 2015)
Pheochromocytomas (PCCs) are rare neuroendocrine tumours that arise from the medulla of the adrenal gland or the sympathetic ganglia and are characterised by the secretion of catecholamines. In 30-40% of patients, PCCs are genetically determined by susceptibility genes as various as RET, VHL and NF1. We have analysed the Ras-Association Domain Family members (RASSFs) in PCCs regarding their inactivating promoter hypermethylation status. Previously we reported a promoter methylation in PCC for the first family member RASSF1A. Promoter hypermethylation of CpG islands leads to the silencing of the according transcript and is a common mechanism for inactivation of tumour suppressors. In this study, we observed inactivating DNA modifications for the RASSF members RASSF2, RASSF5A, RASSF9 and RASSF10, but not for the members RASSF3, RASSF4, RASSF5C, RASSF6, RASSF7 and RASSF8. The degree of promoter methylation was 19% for RASSF2, 67% for RASSF5A, 18% for RASSF9 and 74% for RASSF10. Interestingly, the degree of hypermethylation for RASSF10 in hereditary PCCs was 89% vs. 60% in sporadic PCCs. A similar but less dramatic effect was observed in RASSF5A and RASSF9. Including all RASSF members we found that of 25 PCCs 92% show promoter methylation in at least in one RASSF member. In 75% of the hereditary PCC samples we found two or more methylated RASSF promoters, whereas in sporadic PCCs only 46% were observed. In summary, we could show that in PCC several RASSF members are strongly hypermethylated in their promoter regions and methylation of more than one RASSF member occurs in the majority of PCCs. This adds the inactivation of genes of the RASSF tumour suppressor family to the already known deregulated genes of PCC.